2020
DOI: 10.1002/jcpy.1194
|View full text |Cite
|
Sign up to set email alerts
|

Making the Right Decision: Intensifying the Worth of a Chosen Option

Abstract: When people make decisions, they want the outcomes of their choice to be as positive as possible. But they also want the decision-making process itself to be conducted in the right way. Though this is often described as making decisions that are moral or ethical, it also includes making decisions that are appropriate-that are suitable and fitting. We focus on this latter, overlooked interpretation, and propose that making the right decision is about effectively establishing what is true and real. We discuss th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 103 publications
0
11
0
Order By: Relevance
“…While promotion emphasizes growth and opportunities, prevention emphasizes safety, duty, and security (Crowe & Higgins, 1997). Hence, promotion results in a desire to change the status quo to attain a better state, while prevention results in a desire to maintain a current satisfactory status quo to avoid worse states (Higgins et al, 2020). Promotion results in eager goal pursuit, while prevention results in vigilant goal pursuit (Crowe & Higgins, 1997; Higgins, 1998).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…While promotion emphasizes growth and opportunities, prevention emphasizes safety, duty, and security (Crowe & Higgins, 1997). Hence, promotion results in a desire to change the status quo to attain a better state, while prevention results in a desire to maintain a current satisfactory status quo to avoid worse states (Higgins et al, 2020). Promotion results in eager goal pursuit, while prevention results in vigilant goal pursuit (Crowe & Higgins, 1997; Higgins, 1998).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…According to us, an interesting theory that can be adapted to the study of MADM – with the aim of favoring the sharing of meanings among decision-makers – is that of shared reality ( Echterhoff, 2012 ). Precisely, according to Echterhoff and Higgins (2018) , two well-known exponents of social cognition, shared reality is the experience of having in common with others inner states about the world , that is the perceived relevance of something , as well as feelings , beliefs , or evaluation s. As a result, the perception of inner states’ commonality with others fosters the perceived truth of those inner states and intensifies the experience of making the right decision ( Higgins et al, 2020 ). Therefore, shared reality goes beyond the mere duplication of another person’s emotions, as in the case of emotional contagion 7 ( Neumann and Strack, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the experience of shared reality predicts certainty (Rossignac-Milon, Bolger, Zee, Boothby, & Higgins, 2020); for example, conversation partners discussing ambiguous images who create a greater sense of shared reality feel more certain of what is truly going on in the images. We propose that cleansing behaviors rooted in shared practices feel truly clean, because people believe they clean in the right way (Higgins, Nakkawita, Rossignac-Milon, Pinelli, & Jun, 2020). For example, people colloquially express the belief that their shared cultural practices surrounding toilet routines are cleaner than those of other countries (e.g., people raised to use toilet paper believe that toilet paper is superior to bidets, and vice versa).…”
Section: Introductionmentioning
confidence: 99%